The Silver-Lined Bonds of Sunshine Mining. - Swieringa, Robert J. (The Accounting Review, 1981)
ABSTRACT: Sunshine Mining Company issued silver-indexed bonds in April 1980. This article describes some of the features of these bonds, alternative accounting interpretations, and the company's accounting for the bonds.